Factors associated with low physical activity: a cross-sectional study in workers of a Peruvian clinic - Irene Condori; Fernando Soncco-Llulluy; Jair Li; Jaime Rosales-Rimache (International Journal of Occupational Safety and Health)
Introduction: Low physical activity in workers is an occupational health problem that significantly increases the risk of developing chronic diseases, such as cardiovascular diseases, type 2 diabetes, hypertension, and obesity. This negatively impacts their physical well-being, productivity, and overall quality of life.